European smart citizens as decision makers rather thank data providers - Calzada, I; Keith, M (Urban Transformations, 2016)
On 14 November 2016 the Urban Transformations programme, funded by the Economic and Social Research Council (ESRC), brought together a range of academics and practitioners from across Europe for a knowledge exchange event on smart cities. This workshop, which took place at the Centre for Studies, Media and Telecommunication (SMIT) at the Vrije Universiteit Brussel (VUB), was the first of a series entitled Bridging European Urban Transformations established in partnership with the VUB and its Brussels Centre for Urban Studies, with support from the RSA Smart City–Regional Governance for Sustainability Research Network. In this post-Brexit era, cooperation across borders and disciplines seems more important than ever before. Consequently the series, which runs from November 2016 to October 2017, emphasises the value of connections between institutions and key players in the field of urban transformations, in the UK and in the rest of Europe.